Structural placental changes in women with intra-pregnancy novel coronavirus infection COVID-19 (review) - A. V. Yakimova; S. Yu. Borovaya; V. R. Mukhamedshina; N. S. Datsenko; S. G. Kucherenko; I. M. Pozdnyakov; E. V. Nikitenko (Акушерство, гинекология и репродукция, 2023)
Introduction. During the COVID-19 pandemic, the question regarding an effect of related infection on the body of pregnant women and the fetoplacental complex has emerged, with many aspects of this issue still being unknown. At the moment, it has been proven that in some cases the course of COVID-19 can be accompanied by severe systemic inflammatory reaction leading to hypercoagulable state.Aim: to search for evidence of a direct and/or indirect effect of SARS-CoV-2 infection on human placenta structure.Materials and Methods. Taking into account the goal, this review was compiled according to the type of a narrative review of publications on a topic of interest. A search for English-language publications dated of 01.12.2019 till 01.12.2021 in PubMed/MEDLINE, Cochrane, Web of Science databases was made. The search queries included the following keywords: combinations of «coronavirus» and «infection during pregnancy», «placental structure» and «2019-nCoV», «COVID-19 and pregnancy», «SARSCoV-2 and pregnancy». In the process of writing the article, in order to improve the reader's understanding of the essence of debated issue, there was a need to discuss some of the results with literary sources published earlier 2019 that were not directly related to the topic of the new coronavirus infection (there are 6 such sources). We analyzed full-text publications, both reports on original research and meta-analyses on relevant topics. In total, 351 full-text publications met the query criteria, of which 54 were selected as meeting the objectives of the study. The select reports were discussed by the co-authors, duplicates were excluded and 34 of them were included in this review. In those that were excluded from the review, information about the clinical course of pregnancy and its outcome during novel coronavirus infection prevailed, or isolated cases of studying insignificant placental structural changes were discussed. Studies with a small number of observations were selected only in the case of the uniqueness of the published data, the absence of scientific papers where similar studies would have been conducted in larger sample.Results. Pregnancy complicated by COVID-19 may be accompanied by placental structural changes, which represent both a manifestation of compensatory-adaptive reactions and a consequence of the damaging effect to the placenta due to infectious process. In case of late (in the III trimester) disease in pregnant woman with mild COVID-19, placental disorders are predominantly of compensatory-adaptive nature, specific cytological signs of viral cell damage are uncharacteristic. During COVID-19 infection, chronic histiocytic intervillositis and syncytiotrophoblast necrosis occur more often than in average population, and adverse fetal outcomes are characterized by additional marked increase in intervillous fibrinoid deposition. Before COVID-19 pandemic, chronic histiocytic intervillositis was described in about 6 out of 10,000 placentas (0.6 %) in II and III trimesters.Conclusion. The high frequency of chronic histiocytic intervillositis, both in the placenta of paired women with live-born infants infected prenatally due to maternal virus transmission, and in the placentas of stillborn infected infants, allows us to cautiously assume that such placental structural changes are more characteristic for damage by SARS-CoV-2 rather than other infectious agents. It is necessary to study a relationship between placental structural changes occurred at different gestation ages, as well as clinical course and outcome of pregnancy during COVID-19.